2021
DOI: 10.1186/s12645-020-00074-4
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-enriched Gemini surfactant nanoparticles exhibited tumoricidal effects on human 3D spheroid HT-29 cells in vitro

Abstract: Background Here, we examined the tumoricidal effect of Gemini surfactant nanoparticles enriched with curcumin on 3D spheroid HT-29 cells. The delivery of curcumin and other phytocompounds to the tumor niche is an important challenge. Methods Spheroid HT-29 cells were generated by using a conventional hanging drop method and exposed to different concentrations of Gemini-curcumin nanoparticles. The changes in spheroid integrity and cell viability wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Evidence has shown that delivering the anti-tumor drugs to tumors using engineered exosomes have potential value for clinical applications ( 65 , 66 ). Zibaei et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence has shown that delivering the anti-tumor drugs to tumors using engineered exosomes have potential value for clinical applications ( 65 , 66 ). Zibaei et al.…”
Section: Discussionmentioning
confidence: 99%
“…Zibaei et al. found that curcumin could be loaded into exosomes by a single-step nano-precipitation method, and then exhibited potent tumoricidal effects on colorectal cancer cells ( 67 ). Sun et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The viability of HCT-116 and MEF cells were evaluated after treatment with Gemini surfactant NPs, Chrysophanol, and Gemini-Chr NPs using MTT (3-(4, 5-dimethylthiazole-2-yl)-2, 5- diphenyltetrazolium bromide) method [ 24 ]. In brief, an initial number of 1 × 10 4 cells were suspended in 100 mL of DMEM/HG in each well of 96-well plates containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…An example of this approach is reported in Kim et al (2018a) , where decreasing the temperature to 4 °C led to a significant increase in micropattern area which resulted in spheroid formation within minutes. Hanging drops is another widely used method in which cells are cultured within a suspended drop of medium and aggregate, due to gravity, to its bottom ( Wang et al, 2017 ; Cho et al, 2020 ; Zibaei et al, 2021 ). This technique was developed at the beginning of the twentieth century to visualize small live organisms and study their motility ( Jain, Jain & Jain, 2020 ) and then adapted to the production of spheroids.…”
Section: D Cell Culture Modelsmentioning
confidence: 99%